Human Immunodeficiency Virus (HIV) and Aging: Multimorbidity in Older People With HIV in One Nonurban Southeastern Ryan White HIV/AIDS Program Clinic. (5th December 2020) - Arant, Elizabeth C; Harding, Ceshae; Geba, Maria; Targonski, Paul V; McManus, Kathleen A
Abstract: Background: Age-related chronic conditions are becoming more concerning for people with human immunodeficiency virus (PWH). We aimed to identify characteristics associated with multimorbidity and evaluate for association between multimorbidity and human immunodeficiency virus (HIV) outcomes. Methods: Cohorts included PWH aged 45–89 with ≥1 medical visit at one Ryan White HIV/AIDS Program (RWHAP) Southeastern HIV clinic in 2006 (Cohort 1) or 2016 (Cohort 2). Multimorbidity was defined as ≥2 chronic diseases. We used multivariable logistic regression to assess for associations between characteristics and multimorbidity and between multimorbidity and HIV outcomes. Results: Multimorbidity increased from Cohort 1 (n = 149) to Cohort 2 (n = 323) (18.8% vs 29.7%, P < .001). Private insurance was associated with less multimorbidity than Medicare (Cohort 1: adjusted odds ratio [aOR] = 0.15, 95% confidence interval [CI] = 0.02–0.63; Cohort 2: aOR = 0.53, 95% CI = 0.27–1.00). In Cohort 2, multimorbidity was associated with female gender (aOR, 2.57; 95% CI, 1.22–5.58). In Cohort 1, black participants were less likely to be engaged in care compared with non-black participants (aOR, 0.72; 95% CI, 0.61–0.87). In Cohort 2, participants with rural residences were more likely to be engaged in care compared with those with urban residences (aOR, 1.23; 95% CI, 1.10–1.38). Multimorbidity was not associated with differences in HIV outcomes. Conclusions: Although PWH have access to RWHAP HIV care, PWH with private insurance had lower rates of multimorbidity, which may reflect better access to preventative non-HIV care. In 2016, multimorbidity was higher for women. The RWHAP and RWHAP Part D could invest in addressing these disparities related to insurance and gender. Abstract : At one HIV clinic, multimorbidity prevalence increased among older people with HIV from 2006 to 2016. Private insurance was associated with decreased multimorbidity compared with Medicare in 2006 and 2016, which may reflect better access to preventative non-HIV care.